2012
DOI: 10.4137/cmpsy.s7989
|View full text |Cite
|
Sign up to set email alerts
|

Agomelatine: Its Role in the Management of Major Depressive Disorder

Abstract: Circadian rhythm abnormalities, as shown by sleep/wake cycle disturbances, constitute one the most prevalent signs of depressive illness; advances or delays in the circadian phase are documented in patients with major depressive disorder (MDD), bipolar disorder, and seasonal affective disorder (SAD). The disturbances in the amplitude and phase of rhythm in melatonin secretion that occur in patients with depression resemble those seen in chronobiological disorders, thus suggesting a link between disturbed melat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 195 publications
(216 reference statements)
0
7
0
Order By: Relevance
“…Melatonin's sleep-facilitating properties have been found to be useful for treating insomnia symptoms in elderly and depressive patients. A recently introduced melatonin analog, agomelatine, is also effective for the treatment of major depressive disorder and bipolar affective disorder (Cardinali et al, 2012b).…”
Section: The Sleep-wake Cycle a Window Of The Circadian Timing Systemmentioning
confidence: 99%
“…Melatonin's sleep-facilitating properties have been found to be useful for treating insomnia symptoms in elderly and depressive patients. A recently introduced melatonin analog, agomelatine, is also effective for the treatment of major depressive disorder and bipolar affective disorder (Cardinali et al, 2012b).…”
Section: The Sleep-wake Cycle a Window Of The Circadian Timing Systemmentioning
confidence: 99%
“…It displays an overall selectivity (>100-folds) for MT 1 and MT 2 receptors as compared to other receptor sites.…”
Section: Introductionmentioning
confidence: 99%
“…As AGO addresses sleep disturbances as well as depressive symptoms and has early onset of action, even in severely depressed patients, it stands alone among the antidepressants for effective management of major depressive disorders (MDD) [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies 14 15 16 17 showed that hippocampal volume decreased in patients with stress-related major depression, which might be due to glial and neuronal atrophy or loss related in part to increases in corticosteroids and excitatory amino acids; such relationships have been demonstrated in animal models 18 19 20 , while still under investigation in humans 21 22 . Meanwhile, Agomelatine, a recently marketed antidepressant drug, was reported to induce neurogenesis and cell proliferation in the ventral part of dentate gyrus, resulting to the rapid and early increase in maturation at a critical period of neuronal development, which likely influences the functional integration of new born cells into hippocampal circuitry.…”
mentioning
confidence: 99%